Enhanced thin-film transistor driven high-aperture in-plane switching liquid crystal displays without common line and black matrix - Masahiko Ando (Nature Portfolio, 2021)
Abstract We developed active-matrix in-plane switching liquid crystal displays (IPS-LCDs) with a new vertical structure composed of thin-film transistors (TFTs) that have an aperture ratio of 60% to reduce energy consumption. The novel TFT has a channel and a back channel made of a hydrogenated amorphous-silicon semiconductor layer sandwiched by thin silicon oxide insulating layers. The transfer characteristics are enhanced by uniformly shifting the threshold voltage to be higher than the maximum LC driving voltage (typically > 5 V). The enhanced TFT characteristics provided with a new driving scheme and shielding electrodes enables both the common line and black matrix to be eliminated. We fabricated an IPS TFT-LCD panel with aperture and contrast ratios that are 160% those of the conventional pixel structure.